Establishing an emergency department syndromic surveillance system to support the London 2012 Olympic and Paralympic Games. Issue 12 (25th February 2012) - Elliot, Alex J; Hughes, Helen E; Hughes, Thomas C; Locker, Thomas E; Shannon, Tony; Heyworth, John; Wapling, Andy; Catchpole, Mike; Ibbotson, Sue; McCloskey, Brian; Smith, Gillian E
Abstract : Background: The London 2012 Olympic and Paralympic Games is a mass gathering event that will present a major public health challenge. The Health Protection Agency, in collaboration with the College of Emergency Medicine, has established the Emergency Department Sentinel Syndromic Surveillance System (EDSSS) to support the public health surveillance requirements of the Games. Methods: This feasibility study assesses the usefulness of EDSSS in monitoring indicators of disease in the community. Daily counts of anonymised attendance data from six emergency departments across England were analysed by patient demographics (age, gender, partial postcode), triage coding and diagnosis codes. Generic and specific syndromic indicators were developed using aggregations of diagnosis codes recorded during each attendance. Results: Over 339 000 attendances were recorded (26 July 2010 to 25 July 2011). The highest attendances recorded on weekdays between 10:00 and 11:00 and on weekends between 12:00 and 13:00. The mean daily attendance per emergency department was 257 (range 38–435). Syndromic indicators were developed including: respiratory, gastrointestinal, cardiac, acute respiratory infection, gastroenteritis and myocardial ischaemia. Respiratory and acute respiratory infection indicators peaked during December 2010, concomitant with national influenza activity, as monitored through other influenza surveillance systems. Conclusions: The EDSSS has been established to provide an enhanced surveillance system for the London 2012 Olympics. Further validation of the data will be required; however, the results from this initial descriptive study demonstrate the potential for identifying unusual and/or severe outbreaks of infectious disease, or other incidents with public health impact, within the community.